Hepatic Inflammatory Pseudotumor: Know It to Recognize It - Congedo, Viviana; Fornelli, Adele; Mastrangelo, Laura; Bandini, Giulia; Domanico, Andrea; Accogli, Esterita (Archives of Clinical and Medical Case Reports, 2020)
Inflammatory pseudotumor of the liver (IPTL) is a rare benign lesion that can mimic hepatic malignant neoplasms. A 79-year-old woman, in follow-up care for a left breast cancer, was referred to our Ultrasound Diagnostic Centre for a hepatic mass of unknown nature, displayed on PET-CT, CT and Abdominal Ultrasonography (US). The patient presented with abdominal pain and low-grade fever, increased values of C-Reactive Protein (CRP) and gamma-glutamyl transpeptidase (γGT). Abdominal US confirmed the presence of a heterogeneous polycyclic mass 4.0 × 3.7 cm in size, sub-capsular, localized in the segment VI, isoechoic in arterial phase and hypoechoic in portal and late phase on contrast-enhanced ultrasound (CEUS). A liver biopsy revealed the presence of chronic inflammatory cells without evidence of malignancy. As the patient did not respond to medical therapy, she underwent hepatic segmentectomy and cholecystectomy. At histology, the specimen showed acute and chronic inflammation with xanthogranulomatous features.